A Contrastive study of ’Inversion’ in Modern English and Modern Arabic Poetry - خيري محمد سعيد نادية (Al-Adab Journal, 2018)
The present paper respects ’inversion’ as a habit of arranging the language of modern English and Arabic poetry . Inversion is a significant phenomenon generally in modern literature and particularly in poetry that it treats poetic text as it is a violator to the ordinary text. The paper displays the common patterns and functions of inversion which are spotted in modern English and Arabic poetry in order to show aspects of similarities and differences in both languages. It concludes that inversion is most commonly used in English and Arabic poetry in which it may both satisfy the demands of sound correspondence and emphasis. English and Arabic poetic languages vary in extant to their manipulation of inverted styles as they show changeable frequencies of inversion. Finally , it is notable to mention other significant complementary roles of inversion in this paper as : to shape the aesthetic and the semantic indication , to add ambiguity and lay out to the poems , to represent the state of the poet in writing , and to modify the context . The manipulation of inversion as an information – packaging mechanism ( end focus and new information ) is also another compatible aspect of inversion in both languages. .